Novel silicon carbide integrated power module for EV application - Mouawad, Bassem; Espina, Jordi; Li, Jianfeng; Empringham, Lee; Johnson, Christopher Mark (2018)
The successful penetration of Electric Vehicles (EVs) into the global automotive markets requires the developments of cost effective, high performance and high integration power electronic systems. The present work is concerned with the structural integration of power electronic converters to meet targets for increased power density, improved electrical performance and reduced cost without compromising thermal performance or reliability for EV applications. In particular, a SiC power module to integrate multiple functional elements, i.e. semiconductor devices, DC-link capacitors, output filters, current sensing, and gate driver within a single enclosure sharing a common cooling circuit has been designed and fabricated. Electrical test results showed very smooth waveforms of the outputs, verifying the high frequency switching capacity of the fabricated power module.